Tube Anchor: development of a small medical device from concept to market. Issue 4 (23rd September 2015) - Levy, Andy; Coulthard, Martin; Harvey, Mike; Talbot, Simon; Rich, Graham
Abstract : Experts probably have to immerse themselves in their discipline for at least a decade before they have the knowledge and insights needed to produce world-class work. Medical practitioners with long experience in their specialist fields are particularly well placed to know what type of devices might be needed to make their patients' journeys back to health more comfortable, secure and cost-effective. Medical school curriculae, however, are devoid of formal innovation and business training at least in the UK. The strategies required to convert an idea into reality remain beyond most medical graduates' terms of references, and progressing a 'Eureka moment' is perceived, perhaps understandably, as an overwhelming challenge. Indeed, as exciting, interesting and satisfying though the field can be, medical device development is a complex, time consuming and expensive undertaking requiring more than a fair share of good fortune. Contrary to the impression given by reality television programmes in which budding entrepreneurs pitch their ideas to successful businessmen, funding does not necessarily mean that an idea is worthy of success or destined for it, and vice versa. Equally, the acquisition of intellectual property is in many cases a pyrrhic victory. Using as an example the development of Tube Anchor, a novel device to secure intravenous crystalloid administration tubing, this paper outlines the pathway from concept to a marketed clinical device.